Immigrant entrepreneurship - Sari Pekkala Kerr; William R. Kerr (Bank of Finland, 2016)
We examine immigrant entrepreneurship and the survival and growth of immigrant-founded businesses over time relative to native-founded companies. Our work quantities immigrant contributions to new firm creation in a wide variety of fields and using multiple definitions. While significant research effort has gone into understanding the economic impact of immigration into the United States, comprehensive data for quantifying immigrant entrepreneurship are difficult to assemble. We combine several restricted-access U.S. Census Bureau data sets to create a unique longitudinal data platform that covers 1992-2008 and many states. We describe differences in the types of businesses initially formed by immigrants and their medium-term growth patterns. We also consider the relationship of these outcomes to the immigrants' age at arrival to the United States.
URN:NBN:fi:bof-201612221549
Keywords: F22; J15; J44; J61; L26; M13; O31; O32; O33; 330